Upaya Meningkatkan Minat Baca Siswa Sekolah Dasar Gugus IV Di Kecamatan Koto XI Tarusan - Zelpamailiani Zelpamailiani (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Reading interest has a very important role in the world of education. This study aims to find alternative efforts to increase reading interest in elementary school students in cluster IV in the Koto XI Tarusan sub-district. The low interest in reading in elementary school students is one of the causes of the decline in students' learning motivation. One of the reasons is the lack of interest in reading in the students themselves. In an effort to increase reading interest in elementary school students, students should be given support so that interest in reading arises from the students themselves. If students' reading habits grow from the time students are in elementary school, interest in reading will grow high until students grow up. This research was conducted using a quantitative approach by formulating research problems through references from relevant journals and the like for data analysis. The data obtained were analyzed and compared. Based on the results of the study, it was concluded that efforts to increase the reading interest of elementary school students can be done by fostering reading interest in the students themselves